From Safety Requirements to Just-Enough Safety-Centered Architectural Solutions in Agile Contexts - Leite, Isabella Muniz; Antonino, Pablo Oliveira; Nakagawa, Elisa Yumi (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Safety-critical systems can be found in many sectors of our lives, e.g., in medical equipments and vehicles. A agile practices have been increasingly incorporated into the development processes of these systems, mainly due to demands related to time-to-market and budget reduction. At the same time, recent accidents have shown that various failures have been caused by errors or faults introduced during development and resulted from misunderstandings of safety requirements by agile development teams. Moreover, there is still a lack of techniques for ensuring that safety requirements are properly addressed by both software architecture and implementation. To address this gap, this paper presents the SCA3DA metamodel, which leverages the understanding of safety requirements by agile teams, so that these requirements can be included in the just-enough safety-centered software architecture of safety-critical systems. To demonstrate the applicability of this metamodel, we used it in clinical safety interlock scenarios for infusion pumps. Preliminary results indicate that adopting the SCA3DA metamodel is also feasible in industry projects.